2016
DOI: 10.1002/acn3.322
|View full text |Cite
|
Sign up to set email alerts
|

Deep sequencing of mitochondrial genomes reveals increased mutation load in Friedreich's ataxia

Abstract: ObjectiveFriedreich's ataxia (FRDA) is an autosomal recessive trinucleotide repeat expansion disorder caused by epigenetic silencing of the frataxin gene (FXN). Current research suggests that damage and variation of mitochondrial DNA (mtDNA) contribute to the molecular pathogenesis of FRDA. We sought to establish the extent of the mutation burden across the mitochondrial genome in FRDA cells and investigate the molecular mechanisms connecting FXN downregulation and the acquisition of mtDNA damage.MethodsDamage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 55 publications
(80 reference statements)
1
13
0
Order By: Relevance
“…As previously reported, a number of genes involved in DNA replication and repair are more under-expressed in FRDA cells relative to CTRL cells ( ) ( Bhalla et al, 2016 ; Coppola et al, 2011 ; Haugen et al, 2010 ; Martelli et al, 2007 ). Included in the list of downregulated genes are those encoding the nuclear and mitochondrial DNA glycosylases [ NTHL1 (nth like DNA glycosylase 1), P =5.31E–17; MPG (N-methylpurine DNA glycosylase), P =0.0001; OGG1 (8-oxoguanine DNA glycosylase), P =0.004], DNA endonucleases [ ERCC1 (ERCC excision repair 1, endonuclease non-catalytic subunit), P =0.001; ERCC3 (ERCC excision repair 3, TFIIH core complex helicase subunit), P =0.008], and the DNA damage and replication stress checkpoint protein RAD17 [ RAD17 ( RAD17 checkpoint clamp loader component), P =0.006].…”
Section: Resultssupporting
confidence: 69%
“…As previously reported, a number of genes involved in DNA replication and repair are more under-expressed in FRDA cells relative to CTRL cells ( ) ( Bhalla et al, 2016 ; Coppola et al, 2011 ; Haugen et al, 2010 ; Martelli et al, 2007 ). Included in the list of downregulated genes are those encoding the nuclear and mitochondrial DNA glycosylases [ NTHL1 (nth like DNA glycosylase 1), P =5.31E–17; MPG (N-methylpurine DNA glycosylase), P =0.0001; OGG1 (8-oxoguanine DNA glycosylase), P =0.004], DNA endonucleases [ ERCC1 (ERCC excision repair 1, endonuclease non-catalytic subunit), P =0.001; ERCC3 (ERCC excision repair 3, TFIIH core complex helicase subunit), P =0.008], and the DNA damage and replication stress checkpoint protein RAD17 [ RAD17 ( RAD17 checkpoint clamp loader component), P =0.006].…”
Section: Resultssupporting
confidence: 69%
“…For mtDNA quantitation, genomic DNA was isolated as above. A qPCR quantitation of mtDNA copy number was performed using primers specific to mtDNA sequence or genomic DNA (Bhalla et al, 2016). Abundance of mtDNA relative to genomic DNA was calculated using the 2 −ΔΔCT method (Bhalla et al, 2016).…”
Section: Methodsmentioning
confidence: 99%
“…Indeed, our previous study in FRDA fibroblasts found that low FXN levels led to increased mtDNA damage and decreased mtDNA repair capacity (Bhalla et al, 2016). To determine whether the integrity of mtDNA was compromised in cells expressing only Fxn G127V , we analyzed mtDNA isolated from WT and MUT MEFs using a quantitative PCR assay based on the principle that DNA lesions can slow down or block the progression of DNA polymerase (Bhalla et al, 2016;Ponti et al, 1991;Redmann et al, 2018). This type of assay detects various forms of DNA damage, from single-or double-strand DNA breaks and gaps to specific chemical lesions (Lehle et al, 2014).…”
Section: Mitochondrial Integrity In Fxn G127v Mut Mefs Decreases Overmentioning
confidence: 95%
“…Frataxin deficiency is also linked with mitochondrial DNA (mtDNA) damage (Haugen et al, 2010;Karthikeyan et al, 2003). Indeed, our previous study in FRDA fibroblasts found that low FXN levels led to increased mtDNA damage and decreased mtDNA repair capacity (Bhalla et al, 2016). To determine whether the integrity of mtDNA was compromised in cells expressing only Fxn G127V , we analyzed mtDNA isolated from WT and MUT MEFs using a quantitative PCR assay based on the principle that DNA lesions can slow down or block the progression of DNA polymerase (Bhalla et al, 2016;Ponti et al, 1991;Redmann et al, 2018).…”
Section: Mitochondrial Integrity In Fxn G127v Mut Mefs Decreases Overmentioning
confidence: 99%